THE PURPOSES OF PHYSICAL EDUCATION AND THEIR PRACTICAL IMPLICATIONS - Rolf Kretschmann (Sport Scientific And Practical Aspects, 2025)
Physical education (PE) claims credit for serving multiple purposes such as health, value, or developmental education. Health purposes include physical activity levels and public health approaches. Value purposes contain moral education and lifestyle approaches. Developmental purposes comprise holistic and academic achievement-oriented approaches. This article investigates the various purposes of PE and its practical implications when being absolutized. Scientific evidence regarding each purpose of PE is presented as well. The paper closes with advise for integrating all possible purposes of PE into PE programs.